DETEKSI DINI DAN PENGENALAN TANDA DAN GEJALA KANKER SERVIKS DI PUSTU LERMATANG WILAYAH KERJA PUSKESMAS SAUMLAKI KABUPATEN KEPULAUAN TANIMBAR - Kasmiati, Kasmiati; Arvicha Fauziah; Jakob L. Jambormias; Kristiova M. Saragih (Bajang Institute, 2025)
Cervical cancer is a disease that occurs in the internal genitalia of women, specifically the cervix or the outer surface layer of the cervix/epithelium. Cervical cancer is caused by the Human Papillomavirus (HPV), with the most commonly identified HPV types 16 and 18. Early detection of cervical cancer can be performed with the VIA test, and Pap smear, but the public is generally reluctant to undergo cervical cancer screening due to a lack of knowledge among women, and their families about cervical cancer. The purpose of this outreach activity was to provide participants with knowledge about cervical cancer and how to detect it early. The outreach method used lectures, using material presented in PowerPoint and leaflets. The activity was conducted in 2023 with 38 fertile couples and women of childbearing age participating at the Lermatang Community Health Center (Pustu Lermatang) in the working area of ​​the Saumlaki Community Health Center, Tanimbar Islands Regency. The results showed a significant increase in knowledge of 68.4%. In conclusion, this increase in participant knowledge can serve as a starting point for improving knowledge and willingness to undergo cervical cancer screening with the VIA examination